2019
DOI: 10.1039/c9mt00186g
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of Moco biosynthesis and molybdoenzyme gene expression by molybdenum and iron in bacteria

Abstract: The regulation of the operons involved in Moco biosynthesis is dependent on the availability of Fe–S clusters in the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 257 publications
2
23
0
Order By: Relevance
“…According to previous studies, MoaD-MoaE in molybdenum cofactor (Moco) biosynthesis was able to catalyze some redox reactions in vivo (Zupok et al, 2019). In the present study, we found the expression levels of DRMoaE and DRJAMM are increased simultaneously under oxidative stress, indicating that DRJAMM is necessary for DRMoaE activation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…According to previous studies, MoaD-MoaE in molybdenum cofactor (Moco) biosynthesis was able to catalyze some redox reactions in vivo (Zupok et al, 2019). In the present study, we found the expression levels of DRMoaE and DRJAMM are increased simultaneously under oxidative stress, indicating that DRJAMM is necessary for DRMoaE activation.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, dr_0402 has been found to encode the JAMM/MPN protein, and the product of its expression, DRJAMM, could cleave the MoaD-MoaE fusion protein (DR2607) and generate a C-terminal Gly residue (Yang et al, 2018). MoaD-MoaE is known as the MPT synthase that catalyzes the formation of MPT from cyclic pyranopterin monophosphate (cPMP) converted from 5 -GTP, while the two sulfur molecules on cPMP are carried as thiosulfates on the C-terminal glycine of MoaD (Leimkuhler et al, 2001;Zupok et al, 2019). During the formation of MPT, the substrate pocket of MoaE can bound the cPMP, MPT, and the C-terminal of MoaD.…”
Section: Introductionmentioning
confidence: 99%
“…Two binding sites of CsrA were identified within the moaA promoter region (Patterson-Fortin et al, 2013). For Moco biosynthesis, CsrA was shown to activate the transcription, and it has been suggested that CsrA enhances Moco biosynthesis under conditions of high demand (Zupok et al, 2019b).…”
Section: The Regulation Of Moco Biosynthesismentioning
confidence: 99%
“…In addition, the l-cysteine desulfurase IscS is shared between Fe-S cluster assembly and Moco biosynthesis since it also mobilizes the sulfur for the synthesis of the dithiolene group present in Moco. Further, the expression of most molybdoenzymes and proteins involved in Moco biosynthesis in bacteria is regulated by the transcriptional regulator for fumarate and nitrate reduction, FNR [78,79]. The activity of FNR itself is directly dependent on the availability of Fe-S clusters under anaerobic conditions; consequently, Moco is not synthesized and molybdoenzymes are not expressed when Fe-S clusters are not assembled (Figure 4).…”
Section: Linking Moco Biosynthesis and Fe-s Cluster Assembly In Bacteriamentioning
confidence: 99%